Monetary tightening in the Euro Area: Implications for residential investment - Paul Egan; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2023)
In this paper we assess the implications for housing supply across the Euro Area of the recent tightening in monetary policy. Official monetary policy rates have risen in response to the sustained period of inflation experienced across countries due to the aftermath of the Covid epidemic and the war in the Ukraine. The increase in official rates has been significant and sustained with the European Central Bank (ECB) increasing rates by over 400 basis points in just one year. At the same time, a number of European economies have noted a relative shortage in housing supply as activity levels struggle to keep pace with the increase in housing demand. A period of monetary tightening has significant implications for the residential property market as it can have an adverse impact through both a demand-side channel (reduced affordability for prospective homeowners) and on the supply-side (increase in funding costs for the construction sector). In this paper we address this question by allowing changes in policy rates to impact the residential market through a number of market interest rates. Using a structural VAR approach, we include information on ECB policy rates and two market interest rates; the mortgage and corporate lending rate. Consequently, the change in the official rate operates through both a demand and a supply-side channel. We then examine the implications for housing supply of the contraction in monetary policy across Euro Area countries. Our results indicate that a monetary shock can have a significantly negative impact on housing investment with the effect varying somewhat across countries. The heterogeneity of the impact raises issues concerning the efficacy and efficiency of the monetary policy transmission mechanism.
Keywords: R21; R31; E52; O23; 330; Housing supply; monetary policy